CHAIN REACTIONS AND MECHANISMS OF THESE REACTIONS - Hikmatova Hilola Ilhom qizi; Javharov Jonibek Juraqul o’g’li (Journal of new century innovations, 2024)
Annotation . This quickly statement done from the data with a chain of reactions main purpose and wide spread out reactions that understanding possible _ Chained of reactions types - in gases going all burning reactions , cracking processes , double and _ kept a triangle of hydrocarbons polymerization processes , explosion reactions and another processes enters _ Atom core from energy also chained in use processes very big importance _ Work purpose-chained of reactions to go products and reaction mechanism from learning consists of